The relationship between emotional intelligence and academic achievement for students of the Faculty of Nursing at Tishreen University - اسكندر, مها (Latakia University Journal -Medical Sciences Series, 2020)
This study aimed to assess the relationship between emotional intelligence and academic achievement for students of the Faculty of Nursing at Tishreen University. For this purpose, the researcher used one scale to measure the emotional intelligence, and assess the level of academic achievement for a sample that consisted of (200) students. The largest percentages of them were females, aged 20-22 years, and their academic achievement from (70% to 80%). Results showed that the level of emotional intelligence among the study sample was moderate, and there was a no statistically significant relationship between emotional intelligence and academic achievement. The study recommends to directing educational institutions to pay attention to university students, by encouraging group activities, establishing the concept of discussion and dialogue, which would strengthen the emotional intelligence skills of these students. In addition to working on holding seminars and public lectures to introduce students to the emotional intelligence and its components and its importance in life, social relations and success in All Areas.